A Didática Magna e as transformações pedagógicas que deram origem a pedagogia moderna - Ornelas, Ana Beatriz de Carvalho (Universidade Federal de São Carlos, 2025)
This paper aims to analyze the trajectory and pedagogical legacy of Jan Amos Comenius, highlighting how his personal experiences and the challenges of his time inspired and shaped an innovative vision that contributed to the development of a transformative educational system. His thinking has been revisited by many researchers, and we will observe where the didactics that still inspire educators today began. The specific objective of this article is to structure and point out Comenius’s pedagogical thinking: how it developed, what resources led him to his conclusions, what inspired him from childhood, and how these life experiences enabled him to become one of the pioneers in defending the democratization and universalization of education, regardless of social class. John Amos Comenius is a classical author in the field of education and didactics. Born on March 28, 1592, in Nivnice, Moravia (present-day Czech Republic), he became an orphan at the age of 12 after losing his parents and two sisters to the plague that devastated Europe. He lived with an aunt and was later sent to Prerov to study. He entered the University of Herborn between 1613 and 1614, where he was strongly influenced by Calvinism and Scholasticism—elements that directly shaped his theological and pedagogical thought. This research will be conducted through historical and bibliographic study, based on Comenius’s works and biographies, especially the book The Concept of Theology and Pedagogy in Comenius’s Didactica Magna, by Edson Pereira Lopes. Throughout the text, we will explore the author’s ideas that anticipated modern educational practices, such as teaching in the mother tongue, respecting each child's learning pace, and using images in the teaching-learning process. I conclude by emphasizing that the importance of this research lies in recovering a pedagogical thought that, although born in past centuries, remains essential for reflecting on the quality, access, and equity of education today.
Magna Didactics and the pedagogical transformations that gave rise to modern pedagogy
Keywords: Comenius; Pensamento pedagógico; Teologia e educação; Democratização do ensino; Didática Magna; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO